Glucokinase: evolution, regulatory properties, role in the pathogenesis of type 2 diabetes mellitus - L. A. Kuznetsova; N. E. Basova; A. O. Shpakov (Acta Biomedica Scientifica)
The review examines the evolution, structural and functional organization and regulatory properties of glucokinase, which is predominantly expressed in β-cells of the pancreas and in liver hepatocytes. Considerable attention is paid to the possible role of glucokinase in the etiology and pathogenesis of type 2 diabetes mellitus (T2DM), and the development of approaches to normalize insulin secretion, glucose homeostasis, carbohydrate and lipid metabolism using regulators of glucokinase activity. Data are presented on the influence of variants in the glucokinase gene and glucokinase regulatory protein in the development of disorders of the insulin-secreting function of the pancreas. Thus, inactivating mutations in the glucokinase gene cause T2DM, while activating mutations lead to congenital hyperinsulinism. Data are discussed that L-arginine, allosterically interacting with glucokinase, stimulates insulin secretion and inhibits the degradation of the enzyme, protecting it from ubiquitination. It is concluded that glucokinase and functionally related proteins are promising targets when developing approaches to normalize the sensitivity of pancreatic β-cells to glucose, restore insulin secretion and glucose homeostasis in T2DM and other metabolic disorders. Data for this review were identified by searching MEDLINE, PubMed, and references of articles published in English and Russian between 1966 and 2024.